2019
DOI: 10.3390/cancers11101457
|View full text |Cite
|
Sign up to set email alerts
|

c-Myc Acts as a Competing Endogenous RNA to Sponge miR-34a, in the Upregulation of CD44, in Urothelial Carcinoma

Abstract: MicroRNAs (miRNAs) have been shown to play a crucial role in the progression of human cancers, including urothelial carcinoma (UC), the sixth-most common cancer in the world. Among them, miR-34a has been implicated in the regulation of cancer stem cells (CSCs); however, its role in UC has yet to be fully elucidated. In this study, bioinformatics and experimental analysis confirmed that miR-34a targets CD44 (a CSC surface marker) and c-Myc (a well-known cell cycle regulator) in UC. We found that, surprisingly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Among miRNAs involved in the ceRNA network, miR-34a occupies an important position, which was documented recently in several studies [ 28 , 29 , 30 , 31 ]. Some miR-34a targets have been recently shown to control the function of miR-34a through the ceRNA mechanism.…”
Section: Overview Of Mir-34a Biogenesis and Regulations Of Mir-34amentioning
confidence: 96%
See 1 more Smart Citation
“…Among miRNAs involved in the ceRNA network, miR-34a occupies an important position, which was documented recently in several studies [ 28 , 29 , 30 , 31 ]. Some miR-34a targets have been recently shown to control the function of miR-34a through the ceRNA mechanism.…”
Section: Overview Of Mir-34a Biogenesis and Regulations Of Mir-34amentioning
confidence: 96%
“…Similarly, lnc015192 and lncRNA FEZF1-AS1 act as miR-34a sponges to upregulate ADAM1 expression in breast cancer cells and Notch-1 in glioblastoma, respectively, and, thereby, promoting cancer cell migration [ 29 , 30 ]. C-mycRNA targeting miR-34a acts as a ceRNA and upregulates CD44 expression in urothelial carcinoma [ 31 ].…”
Section: Overview Of Mir-34a Biogenesis and Regulations Of Mir-34amentioning
confidence: 99%
“…The expression of CD44 may be regulated by other epigenetic or posttranslational mechanisms. A recent research in urothelial cancer showed that overexpression of c-Myc upregulates CD44 through a miR-34a -mediated competing endogenous RNA mechanism [ 23 ]. Up to now, the role of CD44 and its variants in EMT is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…26,34,35 We herein demonstrated that CD44 was regulated by ARPP-19 and mediated Herceptin resistance of human HER2-positive gastric cancer cells. Plenty of literatures demonstrated that CD44 played oncogenic roles in various human cancers, [36][37][38][39][40] gastric cancer included. [41][42][43] Furthermore, CD44 was a famous mediator to regulate cancer stem cell-like properties.…”
Section: Discussionmentioning
confidence: 99%